Recursive Inverse Adaptive Filter with second order estimation of autocorrelation matrix - Salman, Mohammad Shukri; Kukrer, Osman; Hocanin, Aykut (IEEE Computer Society help@computer.org, 2010)
The recently proposed Recursive Inverse (RI) Adaptive Filtering algorithm uses a variable step-size and the first order recursive estimation of the correlation matrices in the coefficient update equation which lead to an improved performance. In this paper, a new FIR adaptive filtering algorithm is introduced. This algorithm uses the second order recursive estimation of the correlation matrices in the coefficient update equation which leads to an improved performance over the RI algorithm. The simulation results show that the algorithm outperforms the Transform Domain LMS with Variable Step-Size (TDVSS), the RI and the RLS algorithms in stationary environments. The performance of the algorithms is tested in Additive White Gaussian Noise (AWGN) and Correlated Noise environments. © 2011 IEEE.
Keywords: RI; RLS; TDVSS